THE IMPACT OF SOCIAL MARKETING ON LIBERICA COFFEE BRANDING IN INCREASING CONSUMPTION INTENTION - Gusti Noorlitaria Achmad; Dwi martiyanti; Arvita Rachmawaty; Purwadi; Muhammad Wasil (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
This study aims to analyze the effect of social marketing on consumption intention toward Liberica coffee in East Kalimantan, with branding serving as a mediating variable. As a local commodity, Liberica coffee has considerable potential; however, it remains less favored among the younger generation. Therefore, a social marketing approach is considered strategic in constructing social and emotional narratives that foster awareness, trust, and preference for local products. This study uses quantitative research methods with survey techniques by involving 120 youth respondents in East Kalimantan. The results were calculated by the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The findings show that social marketing has a positive impact on both branding and consumption intention. In addition, brand also plays a strong impact on consumption intention and is found to mediate the relationship of social marketing and consumption intention. The results have theoretical and practical implications for MSME actors, as well as stakeholders to achieve the best social massages wrapped on an authentic and personal branding strategies to increase the consumption of Liberica coffee.